Negotiating Ireland's 'Decade of Centenaries' in the New Age of Brexit. (24th January 2018) - Leary, Peter
Abstract: Ireland is halfway through a 'decade of centenaries' commemorating the series of events that culminated in partition. Contested memories may be further aggravated by Brexit.